2015
DOI: 10.1016/j.neuron.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

RIM-BPs Mediate Tight Coupling of Action Potentials to Ca 2+ -Triggered Neurotransmitter Release

Abstract: Ultrafast neurotransmitter release requires tight colocalization of voltage-gated Ca(2+) channels with primed, release-ready synaptic vesicles at the presynaptic active zone. RIM-binding proteins (RIM-BPs) are multidomain active zone proteins that bind to RIMs and to Ca(2+) channels. In Drosophila, deletion of RIM-BPs dramatically reduces neurotransmitter release, but little is known about RIM-BP function in mammalian synapses. Here, we generated double conditional knockout mice for RIM-BP1 and RIM-BP2, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
218
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(257 citation statements)
references
References 48 publications
(83 reference statements)
24
218
5
Order By: Relevance
“…The RIM/RIM-BP complex has been implicated in enhancing the efficiency of the fusion machinery and the positioning of synaptic vesicles in close proximity to Ca V s to optimize Ca 2+ -secretion coupling (2,5,6). Recently, Acuna et al (8) showed that deletion of RIM-BP1 and RIM-BP2 in the murine Calyx of Held impairs the reliability of evoked neurotransmitter release, presumably due to an uncoupling of Ca V s from release sites. At the Drosophila NMJ, the RIM-BP ortholog DRBP, together with Bruchpilot, is an AZ core component, and elimination of DRBP causes severe structural deficits in AZ organization, associated with strongly impaired basal transmission and STP (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RIM/RIM-BP complex has been implicated in enhancing the efficiency of the fusion machinery and the positioning of synaptic vesicles in close proximity to Ca V s to optimize Ca 2+ -secretion coupling (2,5,6). Recently, Acuna et al (8) showed that deletion of RIM-BP1 and RIM-BP2 in the murine Calyx of Held impairs the reliability of evoked neurotransmitter release, presumably due to an uncoupling of Ca V s from release sites. At the Drosophila NMJ, the RIM-BP ortholog DRBP, together with Bruchpilot, is an AZ core component, and elimination of DRBP causes severe structural deficits in AZ organization, associated with strongly impaired basal transmission and STP (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Acuna et al (8) published a report on the combined loss of RIM-BP1 and RIM-BP2 in mouse synapses. The authors report that although RIM-BPs are not essential for synaptic transmission, AP-triggered neurotransmitter release is more variable and the sensitivity to the Ca 2+ chelator EGTA is increased at the Calyx of Held, suggesting a larger coupling distance of Ca V and the release machinery.…”
mentioning
confidence: 99%
“…release transmitter with low probability. [1][2][3] Here, the number and coupling of VGCCs to synaptic vesicles and the spatio-temporal dynamics of the cytoplasmic cloud of calcium ions following stochastic channel opening has emerged as a key property shaping the presynaptic response after stimulation. In fact, recent evidence has shown that at many fast transmitting presynaptic terminals, only a small number of VGCCs are closely associated with synaptic vesicles via interactions with AZ proteins.…”
mentioning
confidence: 99%
“…In fact, recent evidence has shown that at many fast transmitting presynaptic terminals, only a small number of VGCCs are closely associated with synaptic vesicles via interactions with AZ proteins. 2,4,6 At many of these synapses, vesicle release appears to be triggered by the spatially localized and largely nonoverlapping single channel-derived cloud of calcium ions (nanodomain) after channel opening. 1,3,7 In addition, since VGCC open probability during a brief action potential (p 0 ) is often low, vesicle release is unreliable.…”
mentioning
confidence: 99%
See 1 more Smart Citation